Molybdenum disulfide-based composite positive electrode material applied to aqueous zinc ion light rechargeable battery and preparation method and application of molybdenum disulfide-based composite positive electrode material

By using a layer-by-layer molybdenum disulfide-based composite cathode material coated with 1T phase MoS2, NiO, and 2H phase MoS2 in an aqueous zinc ion photorechargeable battery, the problems of poor reversible cycle performance and low photoelectric conversion efficiency of the existing materials are solved, and efficient and long-life photorechargeable performance is achieved, which is suitable for wearable electronics and portable intelligent electronic devices.

CN120376626AActive Publication Date: 2025-07-25SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510859254.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-07-25
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

The existing positive electrode materials of aqueous zinc ion photorechargeable batteries have problems such as poor reversible cycle performance, low overall photoelectric conversion-energy storage efficiency, slow photocharging rate and expensive material, which limits its application in the fields of wearable electronics and portable intelligent electronics.

Method used

The molybdenum disulfide-based composite positive electrode material coated layer by layer by layer by layer by layer by layer by layer by layer by layer by layer, a 1T phase MoS2 layer, a NiO nanoparticle layer and a 2H phase MoS2 layer are formed on the titanium mesh. The 1T phase MoS2 is used as the metal phase to store zinc, the 2H phase MoS2 is used as the semiconductor for photoelectric conversion, and NiO is used as the hole transport layer material to achieve high-efficiency photocharging.

Benefits of technology

It has achieved reversible multiple photocharging cycle performance, long-life water-based zinc ion photocharging battery, excellent photocharging performance, good dispersion, high photoelectric efficiency, cheap and easy to obtain, and is suitable for market promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120376626A_ABST
    Figure CN120376626A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum disulfide-based composite positive electrode material applied to an aqueous zinc ion light rechargeable battery as well as a preparation method and application of the molybdenum disulfide-based composite positive electrode material. The molybdenum disulfide-based composite positive electrode material comprises a 1T-phase MoS2 layer, a NiO nanoparticle layer and a 2H-phase MoS2 layer which are sequentially coated on a titanium mesh from bottom to top, the 1T-phase MoS2 layer is prepared from 1T-phase MoS2 slurry, the NiO nano-particle layer is prepared from NiO nano-particle slurry, and the 2H-phase MoS2 layer is prepared from 2H-phase MoS2 slurry. The molybdenum disulfide-based composite positive electrode material disclosed by the invention has reversible multi-time photocharging cycle performance and is a potential application material of a long-service-life aqueous zinc ion photocharging battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical fields of materials science and electrochemistry, and particularly relates to a molybdenum disulfide-based composite cathode material for an aqueous zinc-ion photo-charging battery, a preparation method thereof, and an application thereof. Background Art

[0002] An aqueous zinc-ion battery is composed of a zinc metal anode, an aqueous electrolyte, and a zinc storage cathode material. During the constant current charge and discharge process, zinc ions are transported directionally back and forth between the anode and the cathode to achieve the conversion and storage of electrical energy. An aqueous zinc-ion photo-charging battery has basically the same structure as an aqueous zinc-ion battery, and the only difference is that a light-transmitting window is opened on the positive electrode side of the battery to allow light to directly irradiate the surface of the positive electrode material. After the battery completes the constant current discharge, the external current voltage is cut off, and light is applied to it. The battery is charged only by light irradiation. During this process, zinc ions are removed from the interlayer of the positive electrode material and deposited on the surface of the zinc anode to achieve energy storage.

[0003] The biggest difference between an aqueous zinc-ion photo-charging battery and a current conventional photo-charging battery in terms of device structure is that the aqueous zinc-ion photo-charging battery does not have a clearly separated photovoltaic module and energy storage module. Its positive electrode material (only one electrode sheet) serves as both a medium for photovoltaic and energy storage, and simultaneously undergoes the processes of photoelectric conversion and electrical energy storage. This design has advantages such as reducing the device volume, lowering the cost, increasing the integration degree, and reducing the energy loss.

[0004] An aqueous zinc-ion photo-charging battery is an energy storage device that integrates a solar cell and an aqueous zinc-ion energy storage battery in a form without wire connection. As a portable self-powered energy source, it can directly use sunlight for charging. In addition, due to the inherent safety and low cost advantages of aqueous zinc-ion batteries, aqueous zinc-ion photo-charging batteries are considered to be one of the ideal power sources for future wearable electronics, portable intelligent electronics, and other fields. The positive electrode materials of the currently reported aqueous zinc-ion photo-charging batteries are usually prepared based on vanadium oxides, but they generally have problems such as difficulty in reversible cycling, low overall efficiency of photoelectric conversion - energy storage, slow photo-charging rate, and high price of key materials, which limit their further application research and development. Therefore, there is still an urgent need for a photo-charging positive electrode material for aqueous zinc-ion photo-charging batteries that can perform reversible photo-charging cycles, have a long lifespan, high overall efficiency, low price, and high safety. Summary of the Invention

[0005] The object of the present invention is to overcome the deficiencies of the prior art, and provide a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries, a preparation method thereof, and an application thereof. The molybdenum disulfide-based composite cathode material selected by the present invention is prepared layer by layer in the order of 1T-MoS2, NiO, and 2H-MoS2. When used as the positive active material of an aqueous zinc-ion photo-charging battery, the molybdenum disulfide-based composite cathode material has reversible multiple photo-charging cycle performance and is a potential application material for long-life aqueous zinc-ion photo-charging batteries.

[0006] To achieve the above object, the technical solution designed by the present invention is as follows: The present invention provides a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries, wherein the molybdenum disulfide-based composite cathode material comprises a 1T-phase MoS2 layer, a NiO nanoparticle layer, and a 2H-phase MoS2 layer coated on a titanium mesh in sequence from bottom to top; The thickness of the 1T-phase MoS2 layer is 200-300 μm; the thickness of the NiO nanoparticle layer is 40-600 μm; the thickness of the 2H-phase MoS2 layer is 200-300 μm.

[0007] Further, the 1T-phase MoS2 layer is prepared from a 1T-phase MoS2 slurry, and the components of the 1T-phase MoS2 slurry include 1T-phase MoS2, acetylene black, and a PVDF emulsion. Among them, the mass ratio of 1T-phase MoS2, acetylene black, and the PVDF emulsion is 6-8:2:1; The NiO nanoparticle layer is prepared from a NiO nanoparticle slurry, and the components of the NiO nanoparticle slurry include NiO nanoparticles, acetylene black, and a PVDF emulsion. Among them, the mass ratio of NiO nanoparticles, acetylene black, and the PVDF emulsion is 6-8:2:1; The 2H-phase MoS2 layer is prepared from a 2H-phase MoS2 slurry, and the components of the 2H-phase MoS2 slurry include 2H-phase MoS2, acetylene black, and a PVDF emulsion. Among them, the mass ratio of 2H-phase MoS2, acetylene black, and the PVDF emulsion is 6-8:2:1; The mass ratio of the 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticles is 1:1:0.02-1; The solid content of the PVDF emulsion is 9.5-11.5 mg / mL.

[0008] Still further, the mass ratio of 1T-phase MoS2, acetylene black, and the PVDF emulsion is 7:2:1; The mass ratio of NiO nanoparticles, acetylene black, and the PVDF emulsion is 7:2:1; The mass ratio of 2H-phase MoS2, acetylene black, and the PVDF emulsion is 7:2:1; The mass ratio of the 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticles is 1∶1∶0.1.

[0009] The present invention also provides a preparation method of the molybdenum disulfide-based composite cathode material described above, comprising the following steps: (1) Weigh 1T-phase MoS2, acetylene black, and PVDF emulsion according to the mass ratio of the above-mentioned 1T-phase MoS2, acetylene black, and PVDF emulsion, mix and prepare a slurry to obtain a 1T-phase MoS2 slurry; (2) Weigh 2H-phase MoS2, acetylene black, and PVDF emulsion according to the mass ratio of the above-mentioned 2H-phase MoS2, acetylene black, and PVDF emulsion, mix and prepare a slurry to obtain a 2H-phase MoS2 slurry; (3) Weigh NiO nanoparticles, acetylene black, and PVDF emulsion according to the mass ratio of the above-mentioned NiO nanoparticles, acetylene black, and PVDF emulsion, mix and prepare a slurry to obtain a NiO nanoparticle slurry; (4) Weigh the 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticle mass ratio, weigh the 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry; (5) Dropwise coat the 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry on the titanium mesh layer by layer, and dry each layer after dropping to form a 1T-phase MoS2 layer, a NiO nanoparticle layer, and a 2H-phase MoS2 layer on the titanium mesh in sequence, and the molybdenum disulfide-based composite cathode material applied to the aqueous zinc-ion photo-charging battery can be obtained.

[0010] Further, in the step (1), the preparation method of the 1T-phase MoS2 is specifically as follows: 1) Weigh ammonium molybdate tetrahydrate and urea and dissolve them in water, and mix to obtain a clear solution; 2) Transfer the clear solution to a reaction kettle and keep it at 150-170 °C for 22-26 h, and cool to obtain a first black solid product; 3) Wash and dry the first black solid product to obtain 1T-phase MoS2.

[0011] Still further, the mass ratio of the ammonium molybdate tetrahydrate and urea is 2.35-2.55∶3.5-3.7.

[0012] Still further, in the step (2), the preparation method of the 2H-phase MoS2 is as follows: S1: Weigh ammonium molybdate tetrahydrate and urea and dissolve them in water, and mix to obtain a clear solution; S2: Transfer the clarified solution to a reaction kettle, keep it at 210~230 °C for 16~20 h, and obtain the second black solid product after cooling; S3: Wash and dry the second black solid product to obtain 2H-phase MoS2.

[0013] Furthermore, the mass ratio of ammonium molybdate tetrahydrate to urea is 2.35~2.55∶3.5~3.7.

[0014] The present invention also provides an application of the molybdenum disulfide-based composite cathode material in the preparation of an aqueous zinc-ion photo-charging battery.

[0015] The present invention also provides an aqueous zinc-ion photo-charging battery, and the aqueous zinc-ion photo-charging battery includes the molybdenum disulfide-based composite cathode material described above.

[0016] Principle of the present invention: The molybdenum disulfide-based composite cathode material of the present invention is mainly prepared by stacking 1T-phase MoS2, NiO nanoparticles and 2H-phase MoS2 layer by layer. 2H-phase MoS2, as a semiconductor phase that cannot store zinc, plays a role in photoelectric conversion. 1T-phase MoS2, as a metal phase that can store zinc, plays a role in storing zinc ions for energy storage. NiO, as a commonly used hole transport layer material, plays a role in efficiently transporting holes and separating photo-generated carriers between the two phases of MoS2.

[0017] When the molybdenum disulfide-based composite cathode material of the present invention is applied to an aqueous zinc-ion photo-charging battery, the specific photo-charging mechanism is as follows: When light irradiates the surface of 2H-phase MoS2, it undergoes photoelectric conversion, and the photo-generated electrons flow into the external circuit and then enter the zinc negative electrode, inducing zinc metal deposition; the photo-generated holes are transported through NiO into the bulk of 1T-phase MoS2, driving the zinc ions to escape from 1T-phase MoS2, thereby forming a complete photo-charging electrode reaction and realizing energy storage.

[0018] Advantages of the present invention: When the molybdenum disulfide-based composite cathode material of the present invention is selected as the positive electrode of an aqueous zinc-ion photo-charging battery, the positive electrode exhibits reversible photo-charging cycle performance and is a potential application material for long-life aqueous zinc-ion photo-charging batteries. Specifically, under light irradiation with an intensity of 70 mW / cm 2 for 2 hours of photo-charging, and then discharging at a current density of 1000 mA / g, 30 reversible cycles are achieved, and the reversible capacity can reach 67 mAh / g. The process of the present invention is simple, the raw materials are cheap and easy to obtain, the layer-by-layer drop coating method adopted has low requirements for equipment and is easy to scale up production. At the same time, the composite electrode has reversible photo-charging cycle, excellent photo-charging performance, good dispersion of the obtained electrode, high photoelectric efficiency and high yield, which is conducive to market promotion. Description of the Drawings

[0019] Figure 1 XRD pattern of the molybdenum disulfide-based composite cathode material of Example 1; Figure 2 Raman pattern of the molybdenum disulfide-based composite cathode material of Example 1; Figure 3 Photorecharge capacity diagram of the aqueous zinc-ion photorechargeable battery assembled with the molybdenum disulfide-based composite cathode material of Example 1; Figure 4 Photorecharge long cycle diagram of the aqueous zinc-ion photorechargeable battery assembled with the molybdenum disulfide-based composite cathode material of Example 1. Detailed implementation manners

[0020] The present invention will be further described in detail below in conjunction with specific embodiments for the understanding of those skilled in the art.

[0021] Example 1 A preparation method of a molybdenum disulfide-based composite cathode material applied to an aqueous zinc-ion photorechargeable battery specifically includes the following steps: 1) Weigh 2.47 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) powder and 3.60 g of urea (CO(NH2)2) powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1), and continuously stir the obtained solution until it is clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it warm at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in 3) 3 times with deionized water and absolute ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, and finally obtain 1T-phase MoS2 (1T-MoS2) powder; 5) Repeat steps 1) and 2), transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it warm at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in 5) 3 times with deionized water and absolute ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, and finally obtain 2H-phase MoS2 (2H-MoS2) powder; 7) Mix 1T-phase MoS2, acetylene black and PVDF emulsion (solid content 9.5 - 11.5 mg / mL) in a mass ratio of 7:2:1 to prepare a slurry, and obtain a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Then, layer by layer, dropwise coat them onto a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, dry it at 60 °C. In turn, form a 1T-phase MoS2 layer of 200 - 300 μm, a NiO nanoparticle layer of 100 - 200 μm, and a 2H-phase MoS2 layer of 200 - 300 μm on the titanium mesh, thus obtaining a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-rechargeable batteries.

[0022] Example 2 1. Analyze the molybdenum disulfide-based composite cathode material of Example 1 with an X-ray diffractometer. As Figure 1 shown, the crystal form of the molybdenum disulfide-based composite cathode material is stable and the purity of MoS2 is high.

[0023] 2. Analyze the molybdenum disulfide-based composite cathode material of Example 1 with a laser confocal Raman spectrometer (Raman). The results are as Figure 2 shown. It can be confirmed that MoS2 in the molybdenum disulfide-based composite cathode material exists in 1T and 2H phase states respectively, and the phase purity is high.

[0024] 3. Use the molybdenum disulfide-based composite cathode material of Example 1 as the cathode of an aqueous zinc-ion photo-rechargeable battery. The assembly method of the aqueous zinc-ion photo-rechargeable battery is as follows: 1) Cut a round hole with a diameter of 8 mm on the positive electrode shell of a CR2032-type stainless steel battery, and then cut a flexible ITO round sheet with a diameter of 10 mm. Bond the flexible ITO round sheet to the outside of the opened positive electrode shell with ultraviolet curable glue and irradiate it with ultraviolet light for 1 min to complete the encapsulation of the light-rechargeable battery's light-transmitting window; 2) 3 M zinc trifluoromethanesulfonate (Zn(CF3SO3)2) dissolved in deionized water was used as the electrolyte, a zinc sheet as the negative electrode, and the molybdenum disulfide-based composite cathode material of Example 1 as the positive electrode (2H-phase MoS2 was close to the battery case, and 1T-phase MoS2 was close to the inside of the battery), GF-D glass fiber as the separator, and a CR2032-type stainless steel battery case were assembled into a button-type aqueous zinc-ion photo-rechargeable battery.

[0025] 3) The aqueous zinc-ion photo-rechargeable battery of this example was irradiated with light at an intensity of 70 mW / cm 2 to carry out the photo-charging process.

[0026] The results are as Figure 3 shown. The discharge current density was 1 A / g. After 2 h of photo-charging, the voltage of the battery could be raised to 0.8 V, and the reversible capacity could reach 67 mAh / g, which was at a relatively high level among the same type of batteries.

[0027] The results are as Figure 4 shown. In an environment relying only on light charging, the aqueous zinc-ion photo-rechargeable battery of this example was continuously cycled under the condition of 2 h photo-charging, showing a reversible discharge specific capacity and achieving more than 30 reversible photo-charging cycles.

[0028] Example 3 A preparation method of a molybdenum disulfide-based composite cathode material applied to an aqueous zinc-ion photo-rechargeable battery specifically includes the following steps: 1) Weigh 2.47 g of (NH4)6Mo7O 24 ·4H2O powder and 3.60 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Stir the obtained solution continuously until it is clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in 3) 3 times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 1T-phase MoS2 powder; 5) Repeat steps 1) and 2). Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in 5) 3 times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 0.021 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.021 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Then, layer by layer, dropwise coat them onto a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, dry it at 60 °C. A 1T-phase MoS2 layer with a thickness of 200 - 300 μm, a NiO nanoparticle layer with a thickness of 20 - 40 μm, and a 2H-phase MoS2 layer with a thickness of 200 - 300 μm are formed on the titanium mesh in sequence, thus obtaining a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries.

[0029] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, assemble an aqueous zinc-ion photo-charging battery according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example undergoes photo-charging cycling under a light intensity of 70 mW / cm 2 and achieves 30 reversible photo-charging cycles with a reversible capacity of 7.99 mAh / g.

[0030] Example 4 A preparation method of a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries specifically includes the following steps: 1) Weigh 2.47 g of (NH4)6Mo7O 24 ·4H2O powder and 3.60 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Continuously stir the obtained solution until it is clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in 3) three times with deionized water and anhydrous ethanol respectively, and then dry it in a vacuum drying oven at 60 °C to finally obtain 1T-phase MoS2 powder; 5) Repeat steps 1) and 2), transfer the clarified solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in 5) three times with deionized water and anhydrous ethanol respectively, and then dry it in a vacuum drying oven at 60 °C to finally obtain 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, and obtain a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, and obtain a 2H-phase MoS2 slurry containing 1.05 mg of MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, and obtain a NiO nanoparticle slurry containing 0.053 mg of NiO; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.053 mg of NiO, and the 2H-phase MoS2 slurry containing 1.05 mg of MoS2 respectively, and layer-by-layer drop-coat them on a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is drop-coated, dry it at 60 °C. A 1T-phase MoS2 layer with a thickness of 200 - 300 μm, a NiO nanoparticle layer with a thickness of 50 - 100 μm, and a 2H-phase MoS2 layer with a thickness of 200 - 300 μm are formed on the titanium mesh in turn, thus obtaining a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries.

[0031] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, assemble an aqueous zinc-ion photo-charging battery according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example is subjected to a photo-charging cycle under a light intensity of 70 mW / cm 2 to achieve 30 reversible photo-charging cycles, and the reversible capacity is 5.65 mAh / g.

[0032] Example 5 A preparation method of a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries specifically includes the following steps: 1) Weigh 2.47 g of (NH4)6Mo7O24 · 4H2O powder and 3.60 g of CO(NH2)2 powder in a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Continuously stir the resulting solution until it becomes clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain the first black solid product; 4) Wash the first black solid product obtained in 3) three times with deionized water and absolute ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 1T-phase MoS2 powder; 5) Repeat steps 1) and 2). Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain the second black solid product; 6) Wash the second black solid product obtained in 5) three times with deionized water and absolute ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 0.21 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.21 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Dropwise coat them layer by layer on a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, place it in an oven at 60 °C to dry, successively forming a 1T-phase MoS2 layer with a thickness of 200 - 300 μm, a NiO nanoparticle layer with a thickness of 300 - 400 μm, and a 2H-phase MoS2 layer with a thickness of 200 - 300 μm on the titanium mesh, thus obtaining a molybdenum disulfide-based composite cathode material applied to aqueous zinc-ion photo-charging batteries.

[0033] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, an aqueous zinc-ion photocapacitor was assembled according to the method of Example 2. The aqueous zinc-ion photocapacitor of this example was subjected to photocapacitor charging cycles under a light intensity of 70 mW / cm 2 to achieve 30 reversible photocapacitor charging cycles, with a reversible capacity of 21.26 mAh / g.

[0034] Example 6 A method for preparing a molybdenum disulfide-based composite cathode material applied to an aqueous zinc-ion photocapacitor specifically includes the following steps: 1) Weigh 2.47 g of (NH4)6Mo7O 24 ·4H2O powder and 3.60 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1), and continuously stir the obtained solution until it is clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in 3) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 1T-phase MoS2 powder; 5) Repeat steps 1) and 2), transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in 5) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 0.525 mg of NiO nanoparticles; 10) Measure 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, NiO nanoparticle slurry containing 0.525 mg of NiO nanoparticles, and 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Dropwise coat them layer by layer onto a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, dry it at 60 °C. A 1T-phase MoS2 layer with a thickness of 200 - 300 μm, a NiO nanoparticle layer with a thickness of 400 - 450 μm, and a 2H-phase MoS2 layer with a thickness of 200 - 300 μm are formed on the titanium mesh in sequence, thus obtaining a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries.

[0035] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, assemble an aqueous zinc-ion photo-charging battery according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example undergoes photo-charging cycling under a light intensity of 70 mW / cm 2 and achieves 30 reversible photo-charging cycles with a reversible capacity of 34.85 mAh / g.

[0036] Example 7 A preparation method of a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries specifically includes the following steps: 1) Weigh 2.47 g of (NH4)6Mo7O 24 ·4H2O powder and 3.60 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Continuously stir the resulting solution until it is clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 160 °C for 24 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in step 3) 3 times with deionized water and anhydrous ethanol respectively, and then dry it in a 60 °C vacuum drying oven to finally obtain 1T-phase MoS2 powder; 5) Repeat steps 1) and 2). Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 220 °C for 18 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in step 5) 3 times with deionized water and anhydrous ethanol respectively, and then dry it in a 60 °C vacuum drying oven to finally obtain 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 7:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 1.05 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 1.05 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Then, layer by layer, dropwise coat them onto a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, dry it at 60 °C. Sequentially form a 1T-phase MoS2 layer of 200 - 300 μm, a NiO nanoparticle layer of 500 - 600 μm, and a 2H-phase MoS2 layer of 200 - 300 μm on the titanium mesh, thus obtaining a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries.

[0037] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, assemble an aqueous zinc-ion photo-charging battery according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example undergoes a photo-charging cycle under a light intensity of 70 mW / cm 2 and achieves 30 reversible photo-charging cycles with a reversible capacity of 30.23 mAh / g.

[0038] Example 8 A preparation method of a molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries specifically includes the following steps: 1) Weigh 2.35 g of (NH4)6Mo7O 24 ·4H2O powder and 3.70 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Continuously stir the obtained solution until it is clear and transparent, obtaining a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100-mL Teflon reactor, keep it at 150 °C for 26 hours, and then naturally cool it to room temperature to obtain a first black solid product; 4) Wash the first black solid product obtained in 3) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C for drying to finally obtain 1T-phase MoS2 powder; 5) Repeat steps 1) and 2). Transfer the clarified solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 210 °C for 20 hours, and then naturally cool it to room temperature to obtain a second black solid product; 6) Wash the second black solid product obtained in 5) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C for drying to finally obtain 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 6:2:1 to prepare a slurry, and obtain a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 6:2:1 to prepare a slurry, and obtain a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 6:2:1 to prepare a slurry, and obtain a NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Layer by layer, drop-coat them on a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is drop-coated, place it in an oven at 60 °C for drying. A 1T-phase MoS2 layer with a thickness of 200 - 300 μm, a NiO nanoparticle layer with a thickness of 100 - 200 μm, and a 2H-phase MoS2 layer with a thickness of 200 - 300 μm are formed on the titanium mesh in sequence, thus obtaining a molybdenum disulfide-based composite cathode material applied to aqueous zinc-ion photo-charging batteries.

[0039] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, assemble an aqueous zinc-ion photo-charging battery according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example undergoes photo-charging cycling under a light intensity of 70 mW / cm 2 to achieve 30 reversible photo-charging cycles, and the reversible capacity is 17.83 mAh / g.

[0040] Example 9 A preparation method of a molybdenum disulfide-based composite cathode material applied to aqueous zinc-ion photo-charging batteries specifically includes the following steps: 1) Weigh 2.55 g of (NH4)6Mo7O 24 ·4H2O powder and 3.50 g of CO(NH2)2 powder into a glass beaker; 2) Measure 70 mL of deionized water and add it to the glass beaker in step 1). Continuously stir the resulting solution until it becomes clear and transparent to obtain a clear solution; 3) Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 170 °C for 22 hours, and then naturally cool it to room temperature to obtain the first black solid product; 4) Wash the first black solid product obtained in 3) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 1T-phase MoS2 powder; 5) Repeat steps 1) and 2). Transfer the clear solution obtained in step 2) to a 100 mL Teflon reactor, keep it at 230 °C for 16 hours, and then naturally cool it to room temperature to obtain the second black solid product; 6) Wash the second black solid product obtained in 5) three times with deionized water and anhydrous ethanol respectively, and then place it in a vacuum drying oven at 60 °C to dry, finally obtaining 2H-phase MoS2 powder; 7) Mix 1T-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 8:2:1 to prepare a slurry, obtaining a 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2; 8) Mix 2H-phase MoS2, acetylene black, and PVDF emulsion in a mass ratio of 8:2:1 to prepare a slurry, obtaining a 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2; 9) Mix NiO nanoparticles, acetylene black, and PVDF emulsion in a mass ratio of 8:2:1 to prepare a slurry, obtaining a NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles; 10) Measure the 1T-phase MoS2 slurry containing 1.05 mg of 1T-phase MoS2, the NiO nanoparticle slurry containing 0.105 mg of NiO nanoparticles, and the 2H-phase MoS2 slurry containing 1.05 mg of 2H-phase MoS2 respectively. Dropwise coat them layer by layer on a 100-mesh titanium mesh in the order of 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry. After each layer is dropwise coated, place it in an oven at 60 °C to dry, successively forming a 200 - 300 μm 1T-phase MoS2 layer, a 100 - 200 μm NiO nanoparticle layer, and a 200 - 300 μm 2H-phase MoS2 layer on the titanium mesh, thus obtaining a molybdenum disulfide-based composite positive electrode material for aqueous zinc-ion photocatalytic rechargeable batteries.

[0041] Using the molybdenum disulfide-based composite cathode material obtained in this example as the cathode, an aqueous zinc-ion photo-charging battery was assembled according to the method of Example 2. The aqueous zinc-ion photo-charging battery of this example was subjected to photo-charging cycles under a light intensity of 70 mW / cm 2 to achieve 30 reversible photo-charging cycles with a reversible capacity of 35.19 mAh / g.

[0042] Other parts not described in detail are all prior arts. Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments according to this example without creative efforts, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A molybdenum disulfide-based composite cathode material for aqueous zinc-ion photo-charging batteries, characterized in that: The molybdenum disulfide-based composite positive electrode material includes a 1T-phase MoS2 layer, a NiO nanoparticle layer, and a 2H-phase MoS2 layer coated on a titanium mesh in sequence from bottom to top; The thickness of the 1T-phase MoS2 layer is 200 - 300 μm; the thickness of the NiO nanoparticle layer is 40 - 600 μm; the thickness of the 2H-phase MoS2 layer is 200 - 300 μm.

2. The molybdenum disulfide-based composite cathode material according to claim 1, characterized in that: The 1T-phase MoS2 layer is prepared from a 1T-phase MoS2 slurry. The components of the 1T-phase MoS2 slurry include 1T-phase MoS2, acetylene black, and PVDF emulsion. Among them, the mass ratio of 1T-phase MoS2, acetylene black, and PVDF emulsion is 6 - 8∶2∶1; The NiO nanoparticle layer is prepared from a NiO nanoparticle slurry. The components of the NiO nanoparticle slurry include NiO nanoparticles, acetylene black, and PVDF emulsion. Among them, the mass ratio of NiO nanoparticles, acetylene black, and PVDF emulsion is 6 - 8∶2∶1; The 2H-phase MoS2 layer is prepared from a 2H-phase MoS2 slurry. The components of the 2H-phase MoS2 slurry include 2H-phase MoS2, acetylene black, and PVDF emulsion. Among them, the mass ratio of 2H-phase MoS2, acetylene black, and PVDF emulsion is 6 - 8∶2∶1; The mass ratio of the 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticles is 1∶1∶0.02 to 1; The solid content of the PVDF emulsion is 9.5 - 11.5 mg / mL.

3. The molybdenum disulfide-based composite cathode material according to claim 2, wherein: The mass ratio of the 1T-phase MoS2, acetylene black, and PVDF emulsion is 7∶2∶1; The mass ratio of NiO nanoparticles, acetylene black, and PVDF emulsion is 7∶2∶1; The mass ratio of the 2H-phase MoS2, acetylene black, and PVDF emulsion is 7∶2∶1; The mass ratio of the 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticles is 1:1:0.

1.

4. A method for preparing the molybdenum disulfide-based composite cathode material according to claim 2 or 3, characterized in that: It includes the following steps: (1) According to the mass ratio of the above-mentioned 1T-phase MoS2, acetylene black, and PVDF emulsion, weigh 1T-phase MoS2, acetylene black, and PVDF emulsion, mix and configure the slurry to obtain the 1T-phase MoS2 slurry; (2) According to the mass ratio of the above-mentioned 2H-phase MoS2, acetylene black, and PVDF emulsion, weigh 2H-phase MoS2, acetylene black, and PVDF emulsion, mix and configure the slurry to obtain the 2H-phase MoS2 slurry; (3) According to the mass ratio of the above-mentioned NiO nanoparticles, acetylene black, and PVDF emulsion, weigh NiO nanoparticles, acetylene black, and PVDF emulsion, mix and configure the slurry to obtain the NiO nanoparticle slurry; (4)According to the mass ratio of 1T-phase MoS 2、 2H-phase MoS2 and NiO nanoparticles, weigh out 1T-phase MoS2 slurry, NiO nanoparticle slurry and 2H-phase MoS2 slurry; (5) According to the order of the 1T-phase MoS2 slurry, NiO nanoparticle slurry, and 2H-phase MoS2 slurry, layer by layer drop-coat on the titanium mesh, and dry each layer after drop-coating. A 1T-phase MoS2 layer, a NiO nanoparticle layer, and a 2H-phase MoS2 layer are formed on the titanium mesh in sequence, and the molybdenum disulfide-based composite positive electrode material applied to the aqueous zinc-ion photo-charging battery can be obtained.

5. The preparation method according to claim 4, characterized in that: In the step (1), the preparation method of the 1T-phase MoS2 is specifically as follows: 1) Weigh ammonium molybdate tetrahydrate and urea, dissolve them in water, and mix to obtain a clear solution; 2) Transfer the clear solution to a reaction kettle, keep it at 150 - 170 °C for 22 - 26 h, and cool to obtain a first black solid product; 3) Wash and dry the first black solid product to obtain 1T-phase MoS2.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the ammonium molybdate tetrahydrate to the urea is 2.35 - 2.55∶3.5 - 3.

7.

7. The preparation method according to claim 4, characterized in that: In the step (2), the preparation method of the 2H-phase MoS2 is as follows: S1: Weigh ammonium molybdate tetrahydrate and urea, dissolve them in water, and mix to obtain a clear solution; S2: Transfer the clear solution to a reaction kettle, keep it at 210 - 230 °C for 16 - 20 h, and obtain a second black solid product after cooling; S3: Wash and dry the second black solid product to obtain 2H-phase MoS2.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the ammonium molybdate tetrahydrate to the urea is 2.35 - 2.55∶3.5 - 3.

7.

9. Application of the molybdenum disulfide-based composite cathode material according to any one of claims 1 to 3 in the preparation of an aqueous zinc-ion photo-charging battery.

10. A water-based zinc-ion photo-charging battery, characterized in that: The aqueous zinc-ion photo-charging battery comprises the molybdenum disulfide-based composite cathode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Photo-assisted rechargeable zinc ion battery and preparation method thereof

    CN116130253A

  • Preparation method of micron-flower-shaped 1T / 2H-phase molybdenum disulfide wave-absorbing material

    CN117963987A

  • Multi-electrode

    US20240145675A1

  • Phase-controlled nanosheet laminated structure, hybrid composite, and method for manufacturing same

    WO2023121381A1